Socio-Cultural Dynamics and Interethnic Relations: The Chinese-Malay Interface on Rupat Island in the Post-1998 Indonesian Reformation Context - Anju Nofarof Hasudungan; Linda Sunarti (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This study examines the dynamics of relations between ethnic Chinese and Malays on Rupat Island, Bengkalis Regency, Riau Province, in the post-1998 Reformation context and its position as an Indonesia-Malaysia border region. In contrast to major cities such as Jakarta and Medan, which experienced ethnic violence in 1998, Rupat Island demonstrated social stability and intergroup harmony. This study aims to explain the socio-historical factors that support social resilience, identify the cross-cultural adaptation strategies developed, and interpret identity formation and social integration in this multi-ethnic border region. Using a border anthropology approach and descriptive-analytical qualitative methods, this study collected data through in-depth interviews, participant observation, and a review of historical documents and local archives. The analysis was conducted by combining Abner Cohen's (1969) theory of ethnic instrumentalization, Gudykunst and Kim's (2003) cross-cultural adaptation, and Homi Bhabha's (2012) theory of cultural hybridity. The research findings demonstrate that social resilience on Rupat Island does not arise from the absence of conflict, but from an active process of cultural adaptation, ongoing identity negotiation, and the role of local elites in maintaining social balance. The Chinese community's historical adaptation to coastal Malay values, the inclusive local wisdom of the Malay community, and the geographic character of the border, which is open to socio-economic exchange, are key factors in shaping harmony. These findings enrich the study of ethnic relations in Indonesia by demonstrating that economics and identity can serve as vehicles for social integration in border regions.